2007
DOI: 10.4103/1817-1737.33700
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary tuberculosis in non-human immunodeficiency virus-infected adults in an endemic region

Abstract: AIMS:Extrapulmonary tuberculosis (EPTB) still constitutes an important clinical problem. We aimed to evaluate the incidence and features of extrapulmonary tuberculosis.MATERIALS AND METHODS:We retrospectively evaluated 14,266 tuberculosis patients diagnosed between January 1999 and December 2003 in a tertiary care hospital in Istanbul. As many as 2,435 patients (17.1%) with EPTB were evaluated for the incidence and features.RESULTS:Of the 14,266 patients, 4,154 were female (29%) and 10,112 were male (71%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 5 publications
5
29
0
Order By: Relevance
“…A study in Istanbul, Turkey collected patients with extrapulmonary TB from 1999-2003 and found their mean age to be 35±14 years. These patients most commonly presented with pleurisy (66%) [20]. However, in the United States, patient populations tend to be older, as it is usually caused by reactivation of TB [2].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Istanbul, Turkey collected patients with extrapulmonary TB from 1999-2003 and found their mean age to be 35±14 years. These patients most commonly presented with pleurisy (66%) [20]. However, in the United States, patient populations tend to be older, as it is usually caused by reactivation of TB [2].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Cultures of pleural fluid should be taken, but in most series, the cultures are positive in less than 40% of immunocompetent patients [7,20]. Smears should be obtained in immunocompromised hosts, as they are positive in about 20% of HIV-positive individuals [26].…”
Section: Pleural Fluid Stain and Culturementioning
confidence: 99%
“…Tuberculosis was diagnosed in only 4% of acute cases of acute pericarditis [1] Maltezou et al [2] reported 102 children with extrapulmonary tuberculosis; only one had tuberculous pericarditis. The incidence of tuberculosis is frequent in Africans and Asians [3] .…”
Section: Introductionmentioning
confidence: 99%
“…1 It is estimated that about one-third of the world's population is infected with Mycobacterium tuberculosis. 2 Tuberculosis (TB) remains a major global public health problem, despite improved living standards, the availability of free anti-tuberculosis medications, and the implementation of mass Bacillus Calmette-Guerin (BCG) vaccination at birth.…”
Section: Introductionmentioning
confidence: 99%